2023
DOI: 10.3390/buildings14010051
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanical Deterioration Effect of Hard Sandstone Induced by Layer Structure under Uniaxial Compression

Yun Cheng,
Zhanping Song,
Fahong Wu
et al.

Abstract: The deterioration of the surrounding rock at the tunnel bottom is a damage mechanics issue that occurs under disturbance load. To investigate the anisotropic characteristics of mechanical behavior and the AE response mechanism of layered sandstone, uniaxial compression tests and acoustic emission (AE) monitoring were conducted. The results show that the layer structure causes remarkable anisotropic characteristics in the wave velocities. The strain characteristics and mechanical parameters of layered sandstone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It should be indicated that although accurate models have been developed for type I fractures, little is known about type I-II composite fractures under osmotic pressure. The forces acting on rock bodies are usually asymmetric and anisotropic, making compound fractures more common [35][36][37][38][39][40]. Dynamic microcrack growth has a great influence on macroscopic dynamic mechanical properties under impact loadings in brittle solids containing numerous initial microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…It should be indicated that although accurate models have been developed for type I fractures, little is known about type I-II composite fractures under osmotic pressure. The forces acting on rock bodies are usually asymmetric and anisotropic, making compound fractures more common [35][36][37][38][39][40]. Dynamic microcrack growth has a great influence on macroscopic dynamic mechanical properties under impact loadings in brittle solids containing numerous initial microcracks.…”
Section: Introductionmentioning
confidence: 99%